THE ROLE OF CONTEXT IN IMPROVING AI TRANSLATION QUALITY - Nigar Fikrat Habibullayeva (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
This article explores the importance of context in AI-based translation systems. It explains how contextual information improves accuracy, coherence, and fluency while addressing challenges such as ambiguity and cultural differences. The study highlights modern approaches and emphasizes the role of context in future translation technologies.